-12=4(w-5)-6w

Simple and best practice solution for -12=4(w-5)-6w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12=4(w-5)-6w equation:


Simplifying
-12 = 4(w + -5) + -6w

Reorder the terms:
-12 = 4(-5 + w) + -6w
-12 = (-5 * 4 + w * 4) + -6w
-12 = (-20 + 4w) + -6w

Combine like terms: 4w + -6w = -2w
-12 = -20 + -2w

Solving
-12 = -20 + -2w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '2w' to each side of the equation.
-12 + 2w = -20 + -2w + 2w

Combine like terms: -2w + 2w = 0
-12 + 2w = -20 + 0
-12 + 2w = -20

Add '12' to each side of the equation.
-12 + 12 + 2w = -20 + 12

Combine like terms: -12 + 12 = 0
0 + 2w = -20 + 12
2w = -20 + 12

Combine like terms: -20 + 12 = -8
2w = -8

Divide each side by '2'.
w = -4

Simplifying
w = -4

See similar equations:

| -4(3+a)-6(1-a)=8 | | 32=28y+0 | | 12t^3-9t^2+28t=3t^2(4t-3)+7(4t-3) | | 13x+42=4x+5 | | 6y+1.5x=8 | | 2(x-3)+2=4(x+6)-30 | | -2+2p=-14 | | 13y+(4y)(3x)+x= | | 5x+15=15-3x+9 | | 4y-6=-22 | | 2(x-4)+3=4x+7 | | 6x^2+47x+92=0 | | (2x+28)=(3x+137) | | -24-7n=-8(3-6n) | | 42=3(2-3n)-6 | | -19=3(7+3n)+8(8n-5) | | 180=111-u | | -12+19/-7= | | -12+-42/-7= | | 60x^2-20x+1=0 | | 84=2w+2L-3 | | 15y-11y=20 | | -12+-126/-7= | | x^2+(x*y)=120 | | 84+3x=1x | | -9u-5+6=19 | | -12+h/7=6 | | -a+5+6a=1+5a+3 | | -12+h/7= | | 8x+4(2-3x)=36-6x | | (4x-3)+3(3x+6)=5x-1 | | 4x^3-33x^2-30x=0 |

Equations solver categories